2010
DOI: 10.1002/jsfa.4181
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and repellency activity of essential oil of Eucalyptus sp. against Sitophilus zeamais Motschulsky (Coleoptera, Curculionidae)

Abstract: The essential oil of Eucalyptus sp. presented insecticidal and repellency against Sitophilus zeamais Motschulsky (Coleoptera, Curculionidae). Although from an economic point of view synthetic chemicals are still more frequently used as repellents, natural products (essential oils) have the potential to provide efficient and safer repellents for humans and the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 21 publications
4
44
0
8
Order By: Relevance
“…Procópio et al (2003) investigating the PI of six vegetal species upon S. zeamais, verified the better repellence with Eucalyptus citriodora (PI -0.81). Mossi et al (2011), using LD 50 between 0.08 and 0.79 µL/cm 2 , observed PI values from -0.50 until -0.69 for several Eucalyptus spp. Reichert et al (2013) demonstrated that Baccharis dracunculifolia had PI ranging from -0.67 and -0.93 para S. zeamais, when tested in the concentration of 0.06 to 0.65 µL/ cm 2 .…”
Section: Repellence Activitymentioning
confidence: 92%
See 2 more Smart Citations
“…Procópio et al (2003) investigating the PI of six vegetal species upon S. zeamais, verified the better repellence with Eucalyptus citriodora (PI -0.81). Mossi et al (2011), using LD 50 between 0.08 and 0.79 µL/cm 2 , observed PI values from -0.50 until -0.69 for several Eucalyptus spp. Reichert et al (2013) demonstrated that Baccharis dracunculifolia had PI ranging from -0.67 and -0.93 para S. zeamais, when tested in the concentration of 0.06 to 0.65 µL/ cm 2 .…”
Section: Repellence Activitymentioning
confidence: 92%
“…The insects were kept at 25°C (± 2°C) and 75% relative humidity in 1 liter glass bottle containing corn grains (Mossi et al, 2011). The corn used in the experiments was sterilized at -80ºC (24 hours).…”
Section: Creation Development and Maintenance Of S Zeamais S I T O mentioning
confidence: 99%
See 1 more Smart Citation
“…Además, se observó que a medida que se incrementó la dosis de aceite, el número de progenies emergidas fue progresivamente menor, siendo nulo a dosis de 10 y 15 μL a las 72 h de exposición (P < 0.05). Se ha reportado que el uso del aceite de E. globulus disminuye la ovoposición de R. dominica (Batish, PalSingh, Kohli, & Kaur, 2008) y afecta la emergencia de Sitophilus zeamais en granos de maíz causando altas tasas de mortalidad (Mossi et al, 2011). En contraste con E. globulus, la emergencia de progenies de R. dominica en el trigo expuesto al aceite de E. camaldulensis, Table 2 shows the number of insects that emerged from wheat samples exposed to eucalyptus oil vapors.…”
Section: Emergencia De R Dominicaunclassified
“…It was also observed that as the oil dose increased, the number of emerged progenies was progressively lower, being zero at doses of 10 and 15 μL at 72 h of emergence (P < 0.05). It has been reported that the use of E. globulus oil decreases R. dominica oviposition (Batish, Pal-Singh, Kohli, & Kaur, 2008) and affects the emergence of Sitophilus zeamais in maize grains, causing high mortality rates (Mossi et al, 2011). In contrast to E. globulus, emergence of R. dominica progeny in wheat exposed to E. camaldulensis oil, with all volumes evaulated and at all exposure times, was not significantly affected (P < 0.05) ( Table 2).…”
Section: Emergencia De R Dominicamentioning
confidence: 99%